2021
DOI: 10.1080/21655979.2021.1988840
|View full text |Cite
|
Sign up to set email alerts
|

Role of ferroptosis-related genes in Stanford type a aortic dissection and identification of key genes: new insights from bioinformatic analysis

Abstract: Stanford type A aortic dissection (TAAD) is one of the most dangerous vascular diseases worldwide, and the mechanisms of its development remain unclear. Further molecular pathology studies may contribute to a comprehensive understanding of TAAD and provide new insights into diagnostic markers and potential therapeutic targets. Recent studies have identified that ferroptosis, a form of cell death, may play a previously unrecognized role in influencing the development of TAAD. In this study, we explored the path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 60 publications
2
10
0
Order By: Relevance
“…Surprisingly, liproxstatin-1 significantly inhibited BAPN-induced elastic fiber breakage, SMC loss, AD and rupture in mice. Recently, a study demonstrated that ferroptosis may be involved in the occurrence of AD by using bioinformatics analysis [56], while our present study confirmed that ferroptosis of SMCs is an important cause of medial degeneration of the aorta and the progression of AD by conducting experiments in HASMCs, mice and specimens of patients with AD.…”
Section: Discussionsupporting
confidence: 84%
“…Surprisingly, liproxstatin-1 significantly inhibited BAPN-induced elastic fiber breakage, SMC loss, AD and rupture in mice. Recently, a study demonstrated that ferroptosis may be involved in the occurrence of AD by using bioinformatics analysis [56], while our present study confirmed that ferroptosis of SMCs is an important cause of medial degeneration of the aorta and the progression of AD by conducting experiments in HASMCs, mice and specimens of patients with AD.…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, NLR Family Pyrin Domain Containing 3- (NLRP3-) caspase-1 inflammasome could directly cleave and degrade contractile proteins in VSMCs, and NLRP3 or caspase-1 deficiency in mice significantly reduced angiotensin II-induced AD formation [ 32 , 33 ], indicating that pyroptosis in VSMCs contributes to the development of TAAD. Additionally, although direct evidence regarding the role of ferroptosis in AD development is lacking, Zou et al [ 34 ], using bioinformatic analysis, demonstrated differentially expressed ferroptosis-related genes in the normal and TAAD samples. Furthermore, much of the information about necroptosis and AD development has been derived from animal experiments [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Quantitative real-time PCR (qRT-PCR) protocol was as described in our previous study ( 28 ). Briefly, total RNA was extracted from the cells using TRIzol reagent (Invitrogen, United States), and the quality and yield of RNA were evaluated to confirm that the isolated RNA could be used to assess mRNA expression.…”
Section: Methodsmentioning
confidence: 99%
“…Exploring the molecular biology of disease based on the transcriptomes of human pathological tissues may bring the closest realistic insight, which has already been applied in various disease studies and transformed into clinical benefits ( 28 30 ). In this study, we analyzed the differential expression of autophagy-related genes (ARGs) in SCM based on the transcriptomes of human septic heart samples and further explored their potential crosstalk and functional pathways.…”
Section: Introductionmentioning
confidence: 99%